Az élőlények jogalanyiságának környezeti etikai háttere - Bányai, Orsolya (Debreceni Jogi Műhely, 2007)
In the focus of the discipline of environmental ethics stands the moral relationship between human beings and the environment. The development of this science was necessary due to the traditional anthropocentrical approach, which provided an excellent moral base for the exploitation of our natural environment. Although nature was the focus of much of nineteenth and twentieth century philosophy, contemporary environmental ethics only emerged as an academic discipline in the 1970s. Basically two main lines can be distinguished: the invidualistic and the holistic approach. The main idea of individualism (biocentric), similarly to traditional anthropocentrical paradigm, is that only individuals can represent value, which must be respected by others. These individuals are not only human beings, but all living being?, because each individual living thing in nature - whether it is an animal, a plant, or a micro-organism - is a ‘teleological-center-of-life’ having a good or well-being of its own which can be enhanced or damaged, and that all individuals who are teleological-centers-of life have equal intrinsic value (or ‘inherent worth’) which entitles them to moral respect. The holistic approach offers a totally different solution by extending the moral concern to the whole biosphere. Hereinafter this article, along with the most popular disciplines of environmental ethics, examines whether non human beings can have legal standing or not.